Acute presentations of inherited metabolic disorders: investigation and initial management. Issue 3 (March 2019) - Ghosh, Arunabha; Morris, Andrew A M
Abstract: Inborn errors of metabolism are individually rare, but so many have now been described that the general paediatrician will encounter one from time to time. For many, early treatment is important. Unfortunately, most that present acutely do so with non-specific symptoms and signs. It is therefore necessary to identify and investigate those at high risk. The most common problems are neurological (including coma, seizures and stroke-like episodes), hypoglycaemia, disorders of acid-base regulation, acute liver disease, rhabdomyolysis, cardiomyopathy and sudden collapse. Treatment should be started as soon as an inborn error is suspected. This review is a short, practical introduction and cannot cover all situations. If in doubt, consult your local specialist metabolic centre. Free, detailed instructions on the acute management of individual inborn errors of metabolism can be found on the British Inherited Metabolic Disease Group (BIMDG) Website:http://www.bimdg.org.uk/